Fecal miRNA profiles in colorectal cancers with mucinous morphology - Naccarati, Alessio; Dragomir, Mihnea P; Tarallo, Sonia; Gagliardi, Amedeo; Alberini, Virginia; Buchler, Tomas; Liska, Vaclav; Gallo, Gaetano; Vymetalkova, Veronika; Vodickova, Ludmila; Vodicka, Pavel; Pardini, Barbara; et al. (Mutagenesis, 2025)
The diagnostic performance of molecular markers in surrogate tissues like stool may be affected by colorectal cancer (CRC) morphological heterogeneity. The mucinous histotype represents a subgroup of CRC with a peculiar molecular program and unfavorable disease progression. However, the percentage of mucinous morphology necessary to define this subtype is still a matter of debate. In this study, we investigated whether stool miRNA profiles of CRC patients differ in patients with mucinous histopathological subtypes compared to non-mucinous cancers. In this respect, we also explored how the stool miRNA signature reported in our previous multicentric study behaves in this histotype. Small-RNA sequencing was performed in fecal and tissue samples of an Italian cohort (n = 172), including 27 CRC with mucinous morphology (mucinous cancers with ≥ 50% mucinous morphology and those with mucinous component ≥ 5% but < 50%), 58 non-mucinous CRC, and 87 colonoscopy-negative controls. Results were compared with fecal miRNA profiles of a cohort from the Czech Republic (n = 98). Most of the differentially expressed (DE) stool miRNAs (n = 324) were in common between CRC with mucinous morphology and non-mucinous histopathological subtypes in comparison with healthy controls. Interestingly, the altered levels of 25 fecal miRNAs previously identified distinguishing CRC cases from controls in both cohorts were also confirmed after stratification for mucinous morphology. Forty-nine miRNAs were DE exclusively in CRC with mucinous morphology and 61 in non-mucinous CRC. Mucinous cancers and those with mucinous component showed fairly similar profiles that were comparable in the Czech cohort. Among the stool DE miRNAs observed in CRC with mucinous morphology, 20 were also altered in the comparison between tumor and adjacent mucosa tissue. This study highlights miRNAs specifically altered in CRC with mucinous morphology. Nevertheless, the performance of our stool miRNA signature in accurately distinguishing CRC cases from controls was not significantly affected by this histological subtype. This aspect further supports the use of stool miRNAs for noninvasive diagnosis and screening strategies.
Keywords: MicroRNAs; Biomarkers, Tumor; lidé; Middle Aged; nádorové biomarkery; Gene Expression Profiling; Adenocarcinoma, Mucinous; stanovení celkové genové exprese; mikro RNA; Female; Humans; Feces; mucinózní adenokarcinom; Gene Expression Regulation, Neoplastic; lidé středního věku; feces; kohortové studie; Cohort Studies; mužské pohlaví; kolorektální nádory; ženské pohlaví; Colorectal Neoplasms; regulace genové exprese u nádorů; Male; Aged; senioři